Kalanchoe ×oberlanderi (Crassulaceae subfam. Kalanchooideae), a horticulturally successful nothospecies with the Malagasy K. blossfeldiana and K. manginii as parents - Smith, Gideon F. (Phytotaxa, 2023)
One of the horticulturally most popular cultivars of Kalanchoe, K. ‘Margrit’s Magic’, (Crassulaceae subfam. Kalanchooideae) in southern Africa was derived from a hybrid between K. blossfeldiana and K. manginii, two Malagasy species. This nothospecies is here described as K. ×oberlanderi. Reference is made to cultivars that likely have been based on K. ×oberlanderi.